Control and Automation in Citrus Microirrigation Systems - Brian Boman; Steve Smith; Bill Tullos (EDIS)
This is document No. CH194 and Circular 1413, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: July 2002.